2018
DOI: 10.1101/258830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shugoshin is essential for meiotic prophase checkpoints inC. elegans

Abstract: 21 22The conserved factor Shugoshin is dispensable in C. elegans for the two-step loss of sister 23 chromatid cohesion that directs the proper segregation of meiotic chromosomes. We show that 24 the C. elegans ortholog of Shugoshin, SGO-1, is required for checkpoint activity in meiotic 25prophase. This role in checkpoint function is similar to that of the meiotic chromosomal protein, 26 HTP-3. Null sgo-1 mutants exhibit additional phenotypes similar to that of a partial loss of 27 function allele of HTP-3: pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 87 publications
(124 reference statements)
0
5
0
Order By: Relevance
“…htp-3(vc75) is a missense mutation that replaces histidine 96 with a tyrosine in the HORMA domain (H96Y) (Figure 2A). HTP-3 H96Y properly localizes to meiotic chromosomes [42] and does not affect pairing, synapsis and crossover recombination [42,43]. However, we and others previously showed that this mutation in htp-3 abolished meiotic checkpoint responses in C. elegans [42,43].…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…htp-3(vc75) is a missense mutation that replaces histidine 96 with a tyrosine in the HORMA domain (H96Y) (Figure 2A). HTP-3 H96Y properly localizes to meiotic chromosomes [42] and does not affect pairing, synapsis and crossover recombination [42,43]. However, we and others previously showed that this mutation in htp-3 abolished meiotic checkpoint responses in C. elegans [42,43].…”
Section: Resultsmentioning
confidence: 69%
“…HTP-3 H96Y properly localizes to meiotic chromosomes [42] and does not affect pairing, synapsis and crossover recombination [42,43]. However, we and others previously showed that this mutation in htp-3 abolished meiotic checkpoint responses in C. elegans [42,43]. Because of this phenotype, we analyzed HTP-3's relationship with PCH-2 in regulating pairing, synapsis, recombination, and meiotic progression.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations